Extracorporeal membrane oxygenation in the care of a preterm infant with COVID-19 infection: Case report - Patrick-Esteve, Jessica; Mumphrey, Christy; Yu, David; Masoumy, Emily; Lawson, Jeremy; Hebert, David; Barkemeyer, Brian (Frontiers in Pediatrics, 2022)
Coronavirus disease 2019 (COVID-19) was first reported in November 2019 and has since unleashed a global pandemic, with over 518 million cases as of May 10, 2022. Neonates represent a very small proportion of those patients. Among reported cases of neonates with symptomatic COVID-19 infection, the rates of hospitalization remain low. Most reported cases in infants and neonates are community acquired with mild symptoms, most commonly fever, rhinorrhea and cough. Very few require intensive care or invasive support for acute infection. We present a case of a two-month-old former 26-week gestation infant with a birthweight of 915 grams and diagnoses of bronchopulmonary dysplasia and a small ventricular septal defect who developed acute respiratory decompensation due to COVID-19 infection. He required veno-arterial extracorporeal membrane oxygenation support for 23 days. Complications included liver and renal dysfunction and a head ultrasound notable for lentriculostriate vasculopathy, extra-axial space enlargement and patchy periventricular echogenicity. The patient was successfully decannulated to conventional mechanical ventilation with subsequent extubation to non-invasive respiratory support. He was discharged home at 6 months of age with supplemental oxygen via nasal cannula and gastrostomy tube feedings. He continues to receive outpatient developmental follow-up. To our knowledge, this is the first case report of a preterm infant during their initial hospitalization to survive ECMO for COVID-19.